2011
DOI: 10.1590/s1415-43662011001200007
|View full text |Cite
|
Sign up to set email alerts
|

Demanda hídrica e eficiência do uso de água da cana-de-açúcar irrigada no semiárido brasileiro

Abstract: Este trabalho objetivou realizar uma análise da eficiência do uso de água em um sistema de produção de cana-de-açúcar irrigada no Submédio do Vale do São Francisco, Brasil. Indicadores que consideram a resposta produtiva da cultura e o desempenho de aplicação de água no sistema de produção foram utilizados e calculados por meio de dados de biomassa seca acumulada, rendimento industrial e a partir dos valores de evapotranspiração de referência (ETo), evapotranspiração da cultura (ETc) e do volume de água que en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 22 publications
1
7
1
17
Order By: Relevance
“…The results obtained in this study were higher than those found by Silva et al (2011), who estimated WP as a function of sugarcane ETc and obtained a value of 1.22 kg m -3 for the variety RB92579. Gava et al (2011) observed WP for sugarcane of 0.83 to 1.44 kg m -3 , when studying the varieties RB867515, RB855536, and SP80-3280.…”
Section: Water Productivity For Gross Sugar Yield (Wp Gsy )contrasting
confidence: 88%
See 1 more Smart Citation
“…The results obtained in this study were higher than those found by Silva et al (2011), who estimated WP as a function of sugarcane ETc and obtained a value of 1.22 kg m -3 for the variety RB92579. Gava et al (2011) observed WP for sugarcane of 0.83 to 1.44 kg m -3 , when studying the varieties RB867515, RB855536, and SP80-3280.…”
Section: Water Productivity For Gross Sugar Yield (Wp Gsy )contrasting
confidence: 88%
“…For instance, Robertson & Muchow (1994), who performed studies in South Africa, Hawaii, and Australia, reported values between 4.8 and 12.1 kg m -3 . Additionally, there was a study by Rabnawaz When studying water-use efficiency indicators in sugarcane industry, Silva et al (2011) recorded a WP of 9.49 kg m -3 for stems of the variety RB 92579. Singh et al (2007) obtained values for sugarcane plant and ratoon crops of 7.1 and 6.3 kg m -3 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Em base fresca, os dados aqui obtidos (86,8 kg MV ha -1 mm -1 para P e 97,1 kg MV ha -1 mm -1 para ETr, independentemente do clone) foram, em média, superiores àqueles citados por Silva et al (2011) para a cana-deaçúcar (espécie C4) irrigada no Semiárido, que obtiveram 53,6 e 94,9 kg MV ha -1 mm -1 , considerando os valores de rendimento industrial de colmos e, nessa ordem, os valores de P + I (P, precipitação; e, I, irrigação) e de ETc (evapotranspiração da cultura).…”
Section: Resultsunclassified
“…Esse é o período mais crítico no que se refere aos efeitos do déficit hídrico na produtividade, pois é quando as plantas apresentam grande área foliar e necessitam de maior quantidade de água para a realização das trocas gasosas com a atmosfera (GONÇALVES et al, 2010;SILVA et al, 2011a;TRENTIN et al, 2011). Nesta fase, a ocorrência do estresse hídrico acarreta efeitos mais severos na redução das taxas de crescimento do colmo, na produção de fitomassa e no rendimento de sacarose, cujas respostas serão diferentes entre as cultivares (MACHADO et al, 2009;GONÇALVES et al, 2010;GAVA et al, 2011;SILVA et al, 2011b).…”
Section: Introductionunclassified